Structural empowerment, job involvement, and performance: The mediating role of psychological empowerment - Qasemi, Hamid Reza; Shahkarami, Fatemeh (Journal of Accounting, Business and Finance Research, 2024)
This research was conducted with the aim of determining the effect of structural empowerment on job involvement and task performance, while also considering the mediating role of psychological empowerment. The research is of the causal survey type, and the statistical population included all the employees of a government company in the number of 900 people. According to Morgan's table, 269 people were selected as a statistical sample. A questionnaire served as data collection instrument, and Cronbach’s alpha confirmed its validity and reliability. Data analysis was done using the partial least squares method, and hypothesis testing was done using the structural equation method (SEM). We determined the theoretical framework by reviewing the literature and research background, and then formulated two main research hypotheses and four sub-hypotheses. The results of the research hypotheses showed that psychological empowerment has a positive and significant effect on job involvement and psychological empowerment on task performance. We also confirmed the positive and significant effect of structural empowerment on job involvement. The results also showed that structural empowerment on task performance, structural empowerment on task performance through psychological empowerment, and structural empowerment on job engagement through psychological empowerment do not have a positive and significant effect.